2013
DOI: 10.1161/circep.113.000434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Electrocardiographic, Echocardiographic Characteristics and Long-Term Follow-Up of Elite Soccer Players With J-Point Elevation

Abstract: Background-J-point elevation is common in athletes; nevertheless, the influence of structural changes associated with the athlete's heart and its prognostic impact are still debated. Our aim was to investigate the prevalence of J-point elevation, the associated clinical, electrocardiographic, and echocardiographic characteristics and its impact on long-term outcome in elite soccer players. Methods and Results-Clinical, electrocardiographic, and cardiopulmonary exercise test data from 332 male professional socc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…7 In a recent report on professional athletes, a correlation between J-point elevation and interventricular septum thickness was observed, suggesting a possible mechanistic role of exercise-induced left ventricular hypertrophy as the basis for J-point elevation, and no cardiac death was observed in a median of 13 years follow-up. 8 Similarly, in the CARDIA study, the presence of early repolarisation in young adults was not associated with higher risk of death during long-term follow-up. 9 The possibility that false tendons, e.g.…”
Section: Clinical Significancementioning
confidence: 84%
See 1 more Smart Citation
“…7 In a recent report on professional athletes, a correlation between J-point elevation and interventricular septum thickness was observed, suggesting a possible mechanistic role of exercise-induced left ventricular hypertrophy as the basis for J-point elevation, and no cardiac death was observed in a median of 13 years follow-up. 8 Similarly, in the CARDIA study, the presence of early repolarisation in young adults was not associated with higher risk of death during long-term follow-up. 9 The possibility that false tendons, e.g.…”
Section: Clinical Significancementioning
confidence: 84%
“…Inferolateral early repolarisation pattern is seen in 25-35 % of competitive athletes, and inferior only in 4 %, and is considered a dynamic phenomenon related to physical activity. 8,21,22 Finally, a large genome-wide association study has been unable to identify genetic variants associated with the pattern, possibly reflecting the phenotypic heterogeneity that exists among these individuals. 23 It seems, therefore, that the majority of individuals with early repolarisation are at no or minimal risk for arrhythmic events.…”
Section: Clinical Significancementioning
confidence: 99%
“…-familial hyperlipidemia (congenital elevated levels of low-density lipoproteins (LDL) and insufficient levels of high-density lipoproteins (HDL) in the blood), which results in atherosclerotic heart disease [3,4]; -hypertrophic cardiomyopathy [3,8,9]; J. P. Guillem, M. Haissaguerre and co-authors back in 1988 suggested the correlation of ERS with borderline forms of obstructive hypertrophic cardiomyopathy (HCM) on the basis of similar echocardiographic signs (the state of the basal interventricular septum, ventricular hyperkinesia, the movement of the anterior mitral valve, reduction of the area of the outgoing LV tract); -with congenital and acquired heart defects [10]; -connective tissue disorders (СTD) in the form of the appearance of longitudinal, oblique and transverse additional chords in the ventricular cavity of the heart. According to S. N. Shulenin et al [11], in patients with ERS some isolated signs of СTD (dolichomorphy, hypermobility of joints, arachnodactyly, the presence of abnormal chords and mitral valve prolapse) were significantly more often revealed (51 %) than in individuals without this phenomenon (41 %).…”
Section: Aimmentioning
confidence: 99%
“…In a recent retrospective analysis of 118 male soccer players with early repolarization, no cardiac deaths occurred during a mean follow-up of 13.3 years. 69 16, because of RV dominance and repolarization polarity directed posteriorly. 65 In the interpretation of athletes' ECG, it should be stressed that some normal cut-offs differ between the sexes (e.g.…”
Section: Electrical Adaptationmentioning
confidence: 99%